Comparative Study of the Terpenoid Compositions of Himalayan Tahlloid Liverworts - K. Joshi, Prasoon; K. Pant, Anil; Bisht, Manisha; Mathela, C.S. (Asian Journal of Chemistry, 2010)
Himalayan liverworts (Order Marcantiales) were collected from NainitaI and adjoining areas (height: 2000 m) during July to October. The present work on six liverworts is a comparative study of their terpenoid compositions. Wiesnerella denudata (Schiffn.), Cryptomitrium himalayanse (Kash.) and Conocephalum conicum (L. Dum.) are rich in monoterpenoids (hydrocarbons, alcohols and esters) which are repsonsible for their pleasant fragrance. Plagiochasma appendiculatum (L. et L.), Asterella wallichiana (Lehm. et Lindb.) and Targionia hyphophylla (L.) have pleasant smelling sesquiterpenoids, sesquiterpene alcohols in particular. Asterella wallichiana has sesquiterpene alcohols as most exclusive constituents. Wiesnerella denudata and Targionia hypophylla possess sesquiterpene lactones. the wide occurrence of terpenoids offers considerable scope for their use.